Volatile components of Rhizoma Alpiniae Officinarum using three different extraction methods combined with gas chromatographyâmass spectrometry - Zhi-Sheng Xie; Xin-Jun Xu; Chun-Yan Xie; Jie-Yun Huang; Mei Yang; De-Po Yang (Elsevier, 2013)
Volatile components from Rhizoma Alpiniae Officinarum were respectively extracted by three methods including hydrodistillation, headspace solid-phase microextraction (HS-SPME) and diethyl ether extraction. A total of 40 (hydrodistillation), 32 (HS-SPME) and 37 (diethyl ether extraction) compounds were respectively identified by gas chromatographyâmass spectrometry (GC/MS) and 22 compounds were overlapped, including Î±-farnesene, Î³-muurolene, 2,6-dimethyl-6-(4-methyl-3-pentenyl)bicyclo[3.1.1]hept-2-ene, eucalyptol and cadina-1(10), 4-diene and so forth, varying in relative contents. HS-SPME is fast, sample saving and solvent-free and it also can achieve similar profiles as those from hydrodistillation and solvent extraction. Therefore, it can be the priority for extracting volatile components from medicinal plants. Keywords: Rhizoma Alpiniae Officinarum, Volatile components, Hydrodistillation, Headspace solid-phase microextraction, Diethyl ether extraction, Gas chromatographyâmass spectrometry